The benefits of meditation and mindfulness practices during times of crisis such as COVID-19. (14th December 2020) - Behan, C.
Abstract : Meditation and mindfulness are practices that can support healthcare professionals, patients, carers and the general public during times of crisis such as the current global pandemic caused by COVID-19. While there are many forms of meditation and mindfulness, of particular interest to healthcare professionals are those with an evidence base such as mindfulness-based stress reduction (MBSR). Systematic reviews of such practices have shown improvements in measures of anxiety, depression and pain scores. Structural and functional brain changes have been demonstrated in the brains of people with a long-term traditional meditation practice, and in people who have completed a MBSR programme. Mindfulness and meditation practices translate well to different populations across the lifespan and range of ability. Introducing a mindfulness and meditation practice during this pandemic has the potential to complement treatment and is a low-cost beneficial method of providing support with anxiety for all.